Literasi Berita "Cek Fakta sebelum Percaya dan Share Berita" - Irma Yusriani Simamora; Fatma Yulia; Andini Nur Bahri; Yulia Nurul Putri (Al-Balagh : Jurnal Komunikasi Islam, 2022)
Hoaxes exist in a variety of information dissemination contexts, ranging from political to medical issues, from public to private affairs. The existence of the Internet makes it difficult for people to distinguish factual information from hoaxes. The main way to anticipate hoaxes is to educate the public about information flow management. This effort can be made through media education. Efforts that can be made to improve media literacy include performing community service in the form of discussion and knowledge sharing. This community service is achieved by conducting media literacy workshops/training to predict fake news (hoaxes) on social networks, which is a form of active participation and education. university to fix media literacy problems (hoaxes spread), so that people can distinguish between true and false information. which information is false or deceptive. This workshop/training was conducted face to face (face to face) with the attendance of 50 (fifty) Quran recitation participants Griya Fadhilah. In this workshop, theoretical and practical lessons are given on how to check the validity of a report. The result of this workshop is an increase in the knowledge of workshop participants about differentiating factual news and fake news. This can be seen from the reviews of workshop participants